Designing a soft approach for IS planning in the not-for-profit sector: research perspectives and issues - Venable, John; Bhattacharjya, Jyotirmoyee (AUT University, 2007)
In this paper we report on a research project to assist a not-for-profit organisation (NFP) to undertake strategic information systems planning (SISP). The research approach taken was an Action Research project. The project encompassed aspects similar to Design Science Research, in that the SISP method used was developed and adapted to suit the situation and purposes of the situation. In this paper, we summarise the project and findings, then reflect on the research method perspectives adopted and some of the issues that were confronted and some of which remain. The project was undertaken by the second author under the supervision of the first author